Bioenergy from Finnish forests : sustainable, efficient, modern use of wood (International Renewable Energy Agency, 2018)
Wood residues form Finland's main source of bioenergy. About half of the country's wood production is used for heat and power, either through district heating systems or through combined heat and power (CHP) plants. The most modern of these plants use fluidised bed technology to combust or gasify a wide range of forest residues. This report describes Finland's approach to sustainable solid biomass supply based on forest wood resources. The study - prepared by VTT Technical Research Centre of Finland Ltd in close co-operation with the International Renewable Energy Agency (IRENA) - offers insights for other countries on the development of sustainable forest bioenergy. Active management allows carbon storage in forests to grow while more energy is extracted from them. With Finnish forests growing nearly twice as fast as they were in the 1950s, the amount of wood that can be sustainably extracted from them has nearly doubled, the report notes. The other half of Finland's wood production goes mainly to lumber or pulp and paper products, where efficient technologies also help to improve cost-effectiveness and sustainability.